"Allelopathic Effects of Euphorbia helioscopia and Papaver rhoeas on Germination and Initial Seedling Growth of Cereal Crops and Weed seeds" - Khasraw, Muhammed N.; Kamil M. Mustafa; Aziz, Hussein M.; Mustafa, Kawa F.; Ahmad, Saman A.; Khorsheed, Fawzy F. (Sulaimani Journal for Pure and Applied Sciences, 2016)
A laboratory study was conducted to investigate the allelopathic effect of aqueous extracts of fresh roots and leaves of sunspourge and field- poppy weeds on germination and growth of four different plant species; wheat, barley, wild mustard and seabious seeds. Maximum stimulation ratio of germination percentage was observed on barley seeds with sunspourge root extract was 23.46%. Maximum stimulation ratio of wheat root length was 59.16% with sunspourge leaf extract and was 33.02% for barley with field poppy root extract, while poppy leaf extract reduced wild mustard and seabious root length ratio by 37.22% and 29.99% respectively. The highest stimulatory ratio of wheat shoot length was 10.84% with poppy leaf extract at the same time reduced seabious shoot length by 18.52%. Maximum increasing of wheat fresh weight was 88.76% with poppy leaf extract and was 87.94% with sunspourge extract leaf for barley while sunspourge leaf extract decreased wild mustard fresh weight by 77.64%. The highest increasing ratio of barley seedling dry weight recorded with sunspourge leaf extract was 32-85%.
Keywords: allelopathy; germination; cereal crops; weed control